NrnC, an RNase D-Like Protein From Agrobacterium, Is a Novel Octameric Nuclease That Specifically Degrades dsDNA but Leaves dsRNA Intact - Yuan, Zenglin; Gao, Fei; Yin, Kun; Gu, Lichuan (Frontiers in Microbiology, 2019)
NrnC from Agrobacterium tumefaciens (At_NrnC, UniProt accession number A9CG28) is a single DEDDy domain nuclease. Here, we determined the structures of both the apo- and metal ion-bound At_NrnC. The overall structure of At_NrnC protomer is similar to the RNase D exonuclease domain. Unexpectedly, our nuclease assays show that At_NrnC has very different substrate specificity. In contrast to RNase D that degrades single-stranded RNA (ssRNA) and double-stranded RNA (dsRNA), At_NrnC hydrolyses ssRNA, single-stranded DNA (ssDNA) and double-stranded DNA (dsDNA) with high efficiency but cannot degrade dsRNA. Crystal packing and biochemical data show that At_NrnC forms an octameric hollow cylinder structure, which allows ssRNA, ssDNA and dsDNA but not dsRNA to enter the central tunnel where the multiple active sites perform hydrolysis. This novel structural feature confers a high processivity and makes At_NrnC prefer longer dsDNA substrate.